Egyetemi legendárium – emlékek, töredékek a Debreceni Tudományegyetem történetéből - Vincze, László (Gerundium, 2015)
MEMOIRS OF LÁSZLÓ VINCE, PART I. László Vince started his career at the University of Debrecen in 1951 as a stenographer at the Lecture notes oice. After the termination of the oice, from 1952 he worked at he Regsitrar oice of the Arts Faculty, and in 1956 he was transferred to the Rector’s Oice where he worked as a unit director of external afairs (secretary of the rector) between 1972 and 1990, his retirement. During his oice years he gained extensive knowledge ont he history of the university. In 1950s he had contact withthe oicers from the previous era. His detailed but rather subjective memoirs are published in two parts with extensive endnoting.